Methodologic treatment for the contents of inclusive physical education in the subject adapted physical activities - Annia Gómez-Valdés; Bárbara de la C. Roba-Lazo; Santa Ana Pascual-Fis (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2016)
This work came about because of the necessity to introduce the contents relating to Inclusive Physical Education in the subject Adaptive Physical Activity, in form coherently and comprehensive for the students, for there future endeavour of a professional in Physical Culture and Sports; giving them the possibility to know what to do in each moment that the practice physical activities directed to children with Special Educative Needs. This work is structured fundamentally from the usage of activity games in the Introduction, assimilation y evaluation of what is imparted; that permits the indication of forms y didactic strategies that gives them answers to concrete situations in which they have to pay direct attention to the diversity, fostering therefore the respect for the differences in others.